Leadership On Employee Performance - Ema Yudiani; Zarkasi Zarkasi; Huzaemah Huzaemah; Rachmad Ilham; I Nyoman Tri Sutaguna (International Journal of Economics and Management Research, 2023)
This study aims to investigate and evaluate the influence of leadership style and work ethic on workplace interactions. The response sample consisted of around 32 students. The data was collected via sending questionnaires to respondents. Multiple regressive lining is the method of analysis used. When the results of the investigation are positive and suggestive of the patient's responsiveness. The T-Test exposes this as "probability value." The complexity of leadership style is less than 5 percent." This illustrates that the leadership styles adopted by employees are highly advantageous to their work. When the outcome of a workplace disciplinary investigation benefits a student's employment. According to the UJIT study, the degree of question discipline was less than 5 percent alpha. It is therefore evident that workplace discipline is being suppressed.